The Dry and Light Interactive Composite System (DALICS) by Assembled Steel in Vietnam’s Current Construction Industry - Viet Huy, Nguyen Viet Huy; Thuy Linh, Pham Thuy Linh (International Journal of Sustainable Construction Engineering and Technology, 2021)
Since the colonial era, at the beginning of the 20th century, a totally new material started to be used in Vietnam by the French, which is assembled steel. After one hundred years, it occupies a certain position in the field of architecture and construction and development to be the dry and light interactive composite system. In this research, the author especially focuses on assembled steel of the Dry and light interactive composite system (DALICS) method. The aim of this research was to analyze and evaluate the status of the DALICS nowadays in Vietnam, so that predict the orientation of its development in the future. The research method is collect the data, interviewing the stakeholders, and the practical experiment through reality DALICS construction to prove its technologies and benefit. The result is connected with social context to contribute an overall view of Vietnam’s current building industry, therefore, predicts the direction of the assembled steel frame and the DALICS method in the Vietnam building industry in the future.